PELATIHAN MICROSOFT OFFICE SEBAGAI MODAL USAHA JASA PENGETIKAN DI PANTI ASUHAN AL-KAAF JABUNG KABUPATEN MALANG - Herman Hariyadi Ari Murtono; Fitri Fitri; Leonardo Kamajaya; Donny Radianto (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2020)
Microsoft office training in an orphanage is very beneficial both for the students of the orphanage and the administrators of the orphanage. Knowledge of Microsoft Office can be used as a basic asset for typing services at the orphanage so that it can increase income for the orphanage. Al-Kaaf Orphanage, which is located in Jabung, Malang Regency, wants to open a typing service business but is still constrained by the lack of knowledge about basic Microsoft Office. In this service activity, Microsoft Office training will be given at the Al-Kaaf Orphanage. Students of the Al-Kaaf Orphanage will be introduced to MS.Office namely Word, Excel, and Power Point. With this application from MS.Office, it will increase knowledge for students of the Al-Kaaf Orphanage, so that it can be used as the basis for opening a typing service business.